DYNAMICS OF STATISTICAL INDICATORS OF MEDICAL CARE FOR INHABITANTS OF THE REPUBLIC OF CRIMEA IN CASES OF THE GENITOURINARY TRACT NEOPLASMS - V. Y. Startsev; I. Y. Akinshevich (Вестник урологии)
The article presents an analysis of the medical statistical indicators characterizing the state of uro-oncological care for inhabitants of the Crimean Republic. We studied rough indicators of morbidity, morphological verification of tumors, overall mortality of the Crimean population in cases of malignant tumors of urinary system during 2005-2014. Based to the available data about the actual staffing in medical institutions of the Republic of Crimea, we suggested the ways for improving the quality of health care for the Crimean patients with uro-oncological pathology.